Podwyżki - ulotka nr 10 . Price hikes - flier no. 10 - Agencja Informacyjna Solidarności Walczącej. (Agencja Informacyjna Solidarności Walczącej, 1983)
Double-sided, b&w print on white paper. The leaflet, issued on the occasion of a price hike, contains anti-government propaganda focused on its economic record.